Clinical and biological determinants of circulating tumor DNA detection and prognostication using a next-generation sequencing panel assay. Issue 7 (2nd September 2021) - Hsiehchen, David; Espinoza, Magdalena; Gerber, David E.; Beg, Muhammad S.
ABSTRACT: Circulating tumor DNA (ctDNA) is utilized for molecular profiling of cancers, and is under investigation for a growing number of applications based on the assumption that ctDNA levels faithfully reflect disease burden. Our objective was to investigate whether patient and tumor characteristics may impact ctDNA detection or levels and the prognostic significance of ctDNA levels or mutations. We performed a retrospective cohort analysis of a comprehensively annotated cohort of 561 patients at a National Cancer Institute–designated comprehensive cancer center with advanced solid cancers who underwent ctDNA testing using a commercial targeted next-generation sequencing assay. ctDNA detection in advanced cancers was associated with older age, non-obese body mass index, and diabetes, but not with tumor diameter, volume, lesion number, or other pathological features. Regression models indicate that no more than 14.3% of the variance in ctDNA levels between patients was explained by known clinical factors and disease burden. Even after adjusting for established prognostic factors and tumor burden, ctDNA levels were associated with worse survival among patients without prior systemic therapy, while ctDNA mutations were associated with survival among patients who previously received systemic treatment. These findings uncover clinical factors that affect ctDNA detection in patients with advanced cancers and challenge the convention that ctDNA is a surrogate for tumor burden. Our study also indicates that the prognostic value of ctDNA levels and mutations are independent of tumor burden and dependent on treatment context.